2007
DOI: 10.1007/s10461-007-9344-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Discrimination Reported by People Living with HIV in London, UK

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
2
34
0
2
Order By: Relevance
“…Data was recorded using the software program EX-CEL 2013, then exported and analyzed using the STATVIEW version 5.0 SAS Institute (Elford et al, 2012). For the analysis, the rules of descriptive statistics for the calculation of means and proportions of different variables were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was recorded using the software program EX-CEL 2013, then exported and analyzed using the STATVIEW version 5.0 SAS Institute (Elford et al, 2012). For the analysis, the rules of descriptive statistics for the calculation of means and proportions of different variables were used.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Peretti-Watel et al, (2007, showed that 26.28% patients experienced discrimination by medical personnel. Elford, (2012), demonstrated that half of all cases of HIV discrimination were in health care settings. The results of this study revealed that the major manifestations were: blame, insults, maltreatment, and poor health services.…”
Section: Discussionmentioning
confidence: 99%
“…The attitudes of medical health professionals (dentists, physicians and other health care staff) towards treatment of AIDS patients seem to have changed over time and there might be cultural differences in attitudes too. The findings in the literature vary widely, ranging from positive attitudes or appropriate knowledge-in Japan, 1997 [5], Mexico, 1998 [6] [19], and the Netherlands, 2008 [20].…”
Section: Discussionmentioning
confidence: 99%
“…HIV has a high level of stigma [14], and is associated with depression and suicidal thoughts [6]. The stigma related to HIV means that many affected do not disclose to others, feel isolated, and delay reaching out to support organizations [14].…”
Section: Living With Hivmentioning
confidence: 99%
“…The stigma related to HIV means that many affected do not disclose to others, feel isolated, and delay reaching out to support organizations [14]. In addition, there are reports of almost one-third of HIV+ people in England having been discriminated against, and almost half of these individuals have experienced discrimination from healthcare workers [6]. The discrimination in a healthcare setting incurs a distrust of health services and, in particular, the ability of these services and workers to maintain confidentiality [14].…”
Section: Living With Hivmentioning
confidence: 99%